Influence of some natural products of Moringa oleifera (L.) on some biochemical and economical characters of infected mulberry silkworm, Bombyx mori L. (Lepidoptera: Bombycidae) - Hassan, Eman M.; Morsy, Ghada M. A.; Hashish, Mohamed E. (Journal of Phytopathology and Disease Management, 2018)
Bacterial diseases of silkworm, Bombyx mori cause serious problem during silkworm rearing. They cause quantitative and qualitative reduction of silk production. Use of botanical materials having anti-microbial property with no side effects is an alternative way for controlling silkworm diseases. This study aims to shed light on the role of some natural products of Moringa oleifera (seed oil, leaves extract, root powder and honey) with different concentrations in treatment of disease silkworm with bacterial infection, by studying their effects on some protein enzymes Alanine transaminase (ALT), Aspartate transaminase (AST) and protease enzymes, cocoon parameters and silk filament characters of Bombyx mori. At the beginning of the 5th larval instar, larvae were fed on fresh mulberry leaves supplemented with different concentrations of extracts (three diets/day, five times during the 5th larval instar). A significant increase of biochemical aspects (protein transaminases and protease enzyme) in all treatments was observed in comparison with control. Root extracts with concentrations (1% & 2%) and 1.5% of seed oil were the best. Similarly, the cocoon characters (cocoon and shell weights) and silk characters (filament length, weight and size) enhanced significantly in high concentrations. Root and seed oil extracts exhibited the highest significant effect, while no significant differences were noticed among shell weight means. Extracts of the different parts of M. oleifera have a protective and therapeutic execution against bacterial infection of B. mori. Furthermore, a highly significant difference was noticed with root extract using followed by the seed oil treatment with higher concentrations among other treatments.